Additive Inoculation of Influenza Vaccine and 23-Valent Pneumococcal Polysaccharide Vaccine to Prevent Lower Respiratory Tract Infections in Chronic Respiratory Disease Patients - Fujiwara, Hiroshi; Kamimori, Takao; Sumitani, Mitsuhiro; Fujikawa, Terumichi; Tochino, Yoshihiro (Internal Medicine, 2008)
Background An increased incidence of pneumococcal infection triggered by influenza infection has been reported. Objective To examine the effectiveness of the additive inoculation of influenza vaccine (I-V) and 23-valent pneumococcal vaccine (P-V) to prevent lower respiratory tract infections. Methods 105 Japanese patients with chronic respiratory disease underwent the additive inoculation of I-V and P-V between October 2002 and January 2003, and their medical records were used to retrospectively examine the number of bacterial respiratory infections, number of hospitalizations, and length of hospital stay in the 2 years prior to and after P-V inoculation. Among them [chronic obstructive pulmonary disease (COPD): 45; bronchial asthma: 24; bronchiectasis: 20 (including diffuse panbronchiolitis); and other diseases: 16], 98 patients were evaluated, except for seven patients who died of diseases other than respiratory infections within the 2 years after P-V inoculation. Subjects were 51 to 91 years of age (median: 74 yrs), the male-female ratio was 63:42, and 32 patients were on home oxygen therapy. Results After P-V inoculation, decreases in the number of respiratory infections (3.16 vs. 1.95 infections; p=0.0004) and in the number of hospitalizations (0.79 vs. 0.43 hospitalizations; p=0.001) were observed. Furthermore, an analysis including other factors, i.e., number of patients on home oxygen therapy and influenza season, also revealed a decreased number of hospitalizations. Conclusions The additive inoculation of I-V and P-V in Japanese patients with chronic respiratory disease prevented the development of bacterial respiratory infections and warrants further study in patients with respiratory disease.